De vísceras, tejidos e ideas abstractas: pasiones republicanas y figuraciones de lo humano a principios del XIX - Hensel, Franz (El Colegio de México, A.C., 2025)
Perhaps due to their affected nature, political histories have tended to express disdain for the extravagant expressions found in the political language of the nineteenth century. The spectacular collapse of the monarchical universe at the beginning of the century involved the emergence of dizzying experiences regarding the foundation, forms and subjects of the political community and so forms, practices and languages emerged to imagine it and define it, but also contain it. Passions –exacerbated, pursued, liberated– appear stubbornly, repeatedly, obsessively in the political universe of the epoch: “the meekness of the American heart,” “the toxic vapors produced by rancor and spite,” “the unhealed wounds” that “lead men to commit ferocious, remorseless excesses” are common expressions in the political language of the time. The place granted by historical understanding to such an uncomfortable understanding of the human is less clear, however. This article shows that passions –and their particular way of conceiving the human– became an object of calculation and political action, as well as an essential mechanism for understanding the duties and concerns implied by the emergence of unprecedented political orders. In this effort to channel passions as the very possibility of order, complaints about the clergy exacerbated passions regarding the image of a Catholic and republican political community that served as a barrier against a universe that was increasingly ominous and difficult to control.